TRADEMARK PROTECTION IS A PRESSING ISSUE (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article reflects proposals and recommendations related to the legal protection of trademarks within the framework of intellectual property rights, its protection document, national and international legal bases for trademark protection, some issues related to offences and liability in the field, especially ways to adapt national legislation to international norms.
Keywords: trademark, exclusive right, trademark owner, license agreement, counterfeit, material and moral damage, seizure and destruction, fine.